First, we need to find the balanced redox reaction. We can do this by combining the given half-reactions:1. Fe2O3 s + 3H2O l + 2e- -> 2Fe OH 3 s E= -0.33V2. O2 g + 4H+ aq + 4e- -> 2H2O l E= +1.23V3. Fe OH 3 s -> Fe3+ aq + 3OH- aq E= -0.25VFirst, reverse reaction 1 to obtain the Fe2O3 s on the product side:1. 2Fe OH 3 s -> Fe2O3 s + 3H2O l + 2e- E= +0.33VNow, multiply reaction 3 by 2 to balance the number of Fe atoms:3. 2Fe OH 3 s -> 2Fe3+ aq + 6OH- aq E= -0.50VAdd reaction 1 and 3:4. Fe2O3 s + 6OH- aq -> 2Fe3+ aq + 3H2O l + 2e- E= -0.17VNow, multiply reaction 2 by 3/2 to balance the number of O2 molecules:2. 3/2 O2 g + 6H+ aq + 6e- -> 3H2O l E= +1.845VAdd reaction 4 and the modified reaction 2:2Fe s + 3/2 O2 g -> Fe2O3 s E= +1.675VNow we can calculate the standard free energy change G using the formula:G = -nFEwhere n is the number of electrons transferred in this case, 2 , F is Faraday's constant 96,485 C/mol , and E is the standard cell potential.G = -2 * 96,485 * 1.675G = -323,298 J/molThe standard free energy change for the reaction 2Fe s + 3/2 O2 g -> Fe2O3 s at 25C is -323,298 J/mol.